CASE REPORT: INCOMPLETE KAWASAKI DISEASE IN AN INFANT WITH PNEUMONIA - Araújo Quinderé, Júlia (2024)
To report a case of incomplete Kawasaki Disease (KD) with concomitant infection - pneumonia - in infant who was admitted to a secondary hospital of the Unified Health System in the pediatric ward in Fortaleza, Ceará. It is a cross-sectional observational study with descriptive and retrospective elements carried out in January 2024, through electronic medical record review. The assistant team was responsible for the study and used the literature found in UpToDate and MEDLINE as a reference base. It was demonstrated that concomitant infection does not exclude the diagnosis of incomplete KD and that treatment is instituted late - approximately 22.4 days after the onset of fever. The presence of infection did not alter the response to therapy. Incomplete KD must be considered in patients with prolonged febrile illness in an attempt to institute therapy and avoid complications.